PM2.5 from automobile exhaust induces apoptosis in male rat germ cells via the ROS-UPR mt signaling pathway - Cao Wang; Yingchi Zhao; Bin Liu; Zhen Luo; Guangxu Zhou; Kaiyi Mao (PLoS ONE, 2025)
Objective To explore the underlying mechanism behind the fine particulate matter’s (PM2.5)-mediated regulation of reproductive function in male rats, and to determine the role of vitamins in this process. Methods In all, 32 male SD rats were randomized to a control cohort (normal saline), a Vit cohort (vitamin C at 100 mg/kg +  vitamin E at 50 mg/kg), a PM2.5 cohort (PM2.5 10 mg/kg), and a PM2.5 + Vit cohort (PM2.5 exposure +  vitamin C at 100 mg/kg +  vitamin E at 50 mg/kg), with eight rats in each cohort. After four weeks of exposure, mating experiments were carried out. Thereafter, rats were euthanized, and the testis and epididymis tissues were excised for hematoxylin-eosin (HE) staining and sperm quality analysis. Apoptosis of testis tissues was quantified via a terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) assay. Moreover, the testicular oxidative stress (OS)-, apoptosis- and mitochondrial unfolded protein response (UPRmt)-related essential protein expressions were measured via western blotting (WB). Results After PM2.5 exposure, the sperm count and motility decreased, while sperm abnormality and the apoptosis index increased. HE staining showed that the number of spermatogenic cells decreased. WB showed that the PM2.5 group had decreased expressions of superoxide dismutase (SOD), nuclear factor E2-related factor 2 (Nrf2), and B-cell lymphoma-2 (Bcl-2) (p <  0.05), increased expressions of malondialdehyde (MDA), Bcl-2 associated X protein (Bax), and Caspase3 (p <  0.05), and downregulated expressions of C/EBP homologous protein (CHOP), heat shock protein 60 (HSP60), and activating transcription factor 5 (ATF5) (p <  0.05). These were all reversed by vitamin intervention. Conclusion PM2.5 from automobile exhaust disrupts male reproductive function. A combination of vitamins may protect reproductive function via the reactive oxygen species (ROS)-UPRmt signaling pathway.